Bleomycin-loaded folic acid-conjugated nanoliposomes: a novel formulation for targeted treatment of oral cancer - Elham Saberian; Janka Jenčová; Andrej Jenča; Andrej Jenča; Fateme Salehipoor; Hadi Zare-Zardini; Adriána Petrášová; Peter Džupa; Meysam Ebrahimifar; Mohammadreza Allahyartorkaman; Jozef Jenča (Frontiers in Bioengineering and Biotechnology)
IntroductionTargeted delivery of anticancer drugs holds great promise for enhancing therapeutic efficacy while minimizing adverse effects. The folate receptor (FR)-mediated approach offers a selective strategy to target cancer cells overexpressing FR. Bleomycin, an established antitumor antibiotic, suffers from limited efficacy due to poor diffusion into tumor cells. This study examined the anti-cancer potential of folate-targeted liposomal Bleomycin (FL-BLEOMYCIN) in comparison to non-targeted L-BLEOMYCIN on oral cavity cancer (CAL27). The study also investigated FL-Bleomycin’s capacity to halt the cell cycle in the G2/M phase using flow cytometry.MethodsFL-Bleomycin was produced using thin-layer hydration, followed by incorporation of folic acid into nanoliposomes. To evaluate the release profile, drug release tests were carried out. Cytotoxicity of FL-Bleomycin, L-Bleomycin, and traditional Bleomycin was evaluated using cell viability assays. The cell cycle arrest caused by FL-Bleomycin was examined using flow cytometry. Finally, FL-Bleomycin uptake studies were performed to assess the internalization of FL-Bleomycin by CAL27 cells.ResultsCompared to L-Bleomycin and traditional Bleomycin, FL-Bleomycin showed noticeably more cytotoxicity against CAL 27 cells. The effective arrest of CAL 27 cells in the G2/M phase of the cell cycle by FL-Bleomycin was verified by flow cytometry. Uptake studies revealed increased internalization of FL-Bleomycin by CAL 27 cells compared to standard formulations. Drug release studies showed a consistent, non-explosive release profile. Cells treated with these nanoliposomes, compared to control groups, exhibited a dose-dependent decrease in the intensity of the 170-kDa EGF-R band as observed by Western blot analysis.DiscussionThe findings suggest that FL-Bleomycin is a potential method for delivering drugs precisely in tumors expressing folic acid receptors. Its potential for successful cancer treatment is shown by its higher internalization, improved cytotoxicity, and cell cycle prevention in CAL 27 cells. To find out how effective FL-Bleomycin is in vivo and whether it may be used to treat other FR-expressing tumors, more research is necessary.